Trends in Antibiotic Prophylaxis in Oral Surgery - Abdul Wahed; Hammad, Jahangir; Khan, Attal; Zoina; Khan, Sidra; Jan, Rahim; Alam, Maqbool (Indus Journal of Bioscience Research, 2025)
Background: Antibiotic prophylaxis (AP) in oral and maxillofacial surgery aims to prevent postoperative infections, bacteremia-related complications, and systemic sequel such as infective endocarditis. Historically, antibiotics were administered routinely for most surgical dental procedures. However, mounting evidence on limited clinical benefit, the emergence of antimicrobial resistance, and adverse drug reactions has prompted a shift toward selective and evidence-based prophylactic use. Aim: To analyze recent trends in antibiotic prophylaxis in oral surgery, evaluate evidence across common procedures, and summarize evolving international guideline recommendations emphasizing antimicrobial stewardship. Methods: A narrative literature review was conducted using PubMed, Cochrane Library, and relevant dental guideline repositories. Publications from 2000–2025, including randomized controlled trials, systematic reviews, and clinical guidelines, were included. Data on antibiotic regimens, timing, outcomes, and infection rates were extracted and synthesized thematically. Results: Evidence demonstrates a significant decline in routine, multi-day antibiotic prescriptions. Current trends favor single-dose preoperative prophylaxis, typically 2 g amoxicillin orally 1 hour before surgery, especially for dental implant placement and major maxillofacial procedures involving bone grafts or fixation hardware. For simple tooth extractions and routine endodontic surgeries, infection rates remain low (<2%), and prophylaxis offers no statistically significant reduction in postoperative infection. Updated cardiac and orthopedic guidelines restrict prophylaxis to high-risk patients (e.g., prosthetic valves, prior infective endocarditis, select congenital heart diseases, or previous prosthetic joint infections). Stewardship programs have reduced inappropriate antibiotic use by up to 40% in dental practice audits. Emerging alternatives such as chlorhexidine rinses, improved aseptic technique, and individualized risk assessment further reduce the need for systemic antibiotics. Conclusion: Contemporary oral surgery emphasizes risk-based, evidence-driven antibiotic prophylaxis. Single preoperative doses in select cases are favored, while routine or extended courses are discouraged. Adhering to guideline-based practices and stewardship principles ensures patient safety while mitigating antimicrobial resistance.